P140 Peptide Leads to Clearance of Autoreactive Lymphocytes and Normalizes Immune Response in Lupus-Prone Mice - Schall, Nicolas; Talamini, Laura; Wilhelm, Maud; Jouvin-Marche, Evelyne; Muller, Sylviane (Frontiers in Immunology, 2022)
In systemic lupus erythematosus, T cells display multiple abnormalities. They are abnormally activated, secrete pro-inflammatory cytokines, help B cells to generate pathogenic autoantibodies, and provoke the accumulation of autoreactive memory T cells. P140, a synthetic peptide evaluated in phase-III clinical trials for lupus, binds HSPA8/HSC70 chaperone protein. In vitro and in vivo, it interferes with hyperactivated chaperone-mediated autophagy, modifying overexpression of major histocompatibility complex class II molecules and antigen presentation to autoreactive T cells. Here, we show that in P140-treated lupus mice, abnormalities affecting T and B cells are no longer detectable in secondary lymphoid tissue and peripheral blood. Data indicate that P140 acts by depleting hyper-activated autoreactive T and B cells and restores normal immune homeostasis. Our findings suggest that P140 belongs to a new family of non-immunosuppressive immunoregulators that do not correct T and B cells abnormalities but rather contribute to the clearance of deleterious T and B cells.